Multiscale modelling and measurements for powder compaction. - Jinnil Lee Choi (2007)
In this thesis, experimental investigations into friction between powder and die (macro scale), numerical modelling of a micro scale friction measurement method by atomic force microscopy, and numerical modelling of compaction and friction processes at a micro scale are presented. The experimental work explores friction mechanisms by using an extended sliding plate apparatus for low load running over a longer distance to measure frictional characteristics between powder compact and target surface with variation of powders, loads, surface finishes, and speed. The behaviour of the static and dynamic friction of both ductile and brittle powders was explored and important factors in the friction mechanisms were identified with regard to particle size, particle shape, material response (ductile or brittle), and surface topography. Numerical modelling of AFM experiment is presented with the aim of exploring friction mechanisms at the micro scale. As a starting point for this work, comparisons between FE (finite element) models and previously reported mathematical models for stiffness calibration of cantilevers (beam and V-shaped) are presented and discrepancies highlighted. A colloid probe1 model was developed and its normal and shear interaction were investigated exploring the response of the probe accounting for inevitable imperfections in its manufacture. The material properties of the cantilever had significant impact on both normal and lateral response, even local yielding was found in some areas. The sensitivity of the response in both directions was explored and found that it was higher in normal than in lateral. In lateral measurement, generic response stages were identified, comprising a first stage of twisting, followed by lateral bending, and then slipping. This was present in the two cantilever types explored (beam and V-shaped). Additionally, an emulation model was designed to explore dynamic sensitivity by comparing the simulation of a hysteresis loop with previously reported experiment and the results show good agreement in response pattern. The ability to simulate the scan over an inclined surface representing the flank of an asperity was also demonstrated. The compaction stage of the experiment was numerically modelled using a combined discrete and finite element modelling scheme to explore compaction mechanisms further. A number of simulation factors and process parameters were investigated. Comparisons were made with previously published work showed reasonable agreement and the simulations were then used to explore process response to the range of particle scale factors. Models comprising regular packing of round particles exhibited stiff response with high initial density. Models with random packing were explored to account for a more practical initial density and this was confirmed. Numerical modelling of the compaction stage was extended to account for the shearing stage of the extended sliding plate experiment. This allowed micro scale simulations of the friction mechanisms seen within the experimental programme. The frictional response with similar stress level in the normal direction as reported for the experiment was first emulated and explored and qualitative agreement was achieved showing similar pattern. The factors identified from the experiments were considered and explored on smooth and rough surfaces highlighting each effect. It was confirmed that the rough surface clearly leads to higher friction coefficient since it accounts for both plain friction and topographical effects and the average stress distribution increased against the restraining die wall when the rough surface was introduced for the model with round regular packing of particles. Random packed models again showed a better reflection of the experimental conditions. A wider distribution of stress was observed because of the further rearrangements. Interlocking was observed for the models with irregular shaped particles on a rough surface, which led to increase in normal stress on the top punch. This would lead to dilation in the case where a punch was force level controlled as for the experiment.